Is team confidence the key to success? The reciprocal relation between collective efficacy, team outcome confidence, and perceptions of team performance during soccer games - Fransen, K.; Decroos, S.; Vanbeselaere, N.; vande Broek, G.; de Cuyper, B.; Vanroy, J.; Boen, F. (Journal of Sports Sciences, 2015)
The present manuscript extends previous research on the reciprocal relation between team confidence and perceived team performance in two ways. First, we distinguished between two types of team confidence; process-oriented collective efficacy and outcome-oriented team outcome confidence. Second, we assessed both types not only before and after the game, but for the first time also during half-time, thereby providing deeper insight into their dynamic relation with perceived team performance. Two field studies were conducted, each with 10 male soccer teams (N = 134 in Study 1; N = 125 in Study 2). Our findings provide partial support for the reciprocal relation between players` team confidence (both collective efficacy and team outcome confidence) and players` perceptions of the team`s performance. Although both types of players` team confidence before the game were not significantly related to perceived team performance in the first half, players` team confidence during half-time was positively related to perceived team performance in the second half. Additionally, our findings consistently demonstrated a relation between perceived team performance and players` subsequent team confidence. Considering that team confidence is a dynamical process, which can be affected by coaches and players, our findings open new avenues to optimise team performance.